Gambaran Faktor Penyebab Kejadian Ketuban Pecah Dini di RSU Ananda Purwokerto - Shiddiqiyah, Nurinnisa; Utami, Tin; Sukmaningtyas, Wilis (Universitas Harapan Bangsa Purwokerto, 2022)
Premature rupture of membranes (PROM) is one of the causes of infection which poses a serious threat to the welfare and health of the mother and fetus. It is proven in Indonesia that PROM is the highest disorder in childbirth complications. Several factors cause PROM such as parity, fetal position abnormalities, anemia, and so on. This study aims to describe the causes of premature rupture of membranes at Ananda General Hospital, Purwokerto. This research method is descriptive quantitative in retrospective approach. The population in this study is all medical record data for mothers giving birth with premature rupture of membranes at Ananda General Hospital Purwokerto in 2021, namely a total of 113 respondents using the total sampling technique so that the sample is 113 respondents. The type of data used is secondary data. The data analysis used is univariate analysis. Based on the results of the study, it was found that the majority age factor was mothers aged 20-35 years (92%), the majority parity factor was primiparous mothers (56.6%), the majority gestational age factor was term pregnancy (≥ 37 weeks) as many as ( 88.5%), the majority of fetal position abnormalities were head presentation (89.4%), the majority of anemia factors were not anemia (65.5%). There is still a high incidence of PROM from various causative factors, therefor it is hoped that health workers can provide the latest counseling from the results of this study and it is hoped that pregnant women will routinely carry out antenatal care in health services